2020
DOI: 10.1038/s41598-020-70733-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of metals dysregulation in patients with systolic and diastolic dysfunction in ischemic heart disease

Abstract: ischemic heart disease (iHD) is the leading cause of death and chronic disability in the world. iHD affects both the systolic and diastolic function of the heart which progressively leads to heart failure; a structural and functional impairment of filling or ejection of blood from the heart. In this study, the progression of systolic and diastolic dysfunction characterized according to their echocardiographic parameters including left ventricular ejection fraction (EF), grades of diastolic dysfunction and rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“… 32 In another human study of 62 patients, chromium levels were found significantly higher in patients with systolic ischemic heart disease. 33 The exact mechanisms of how chromium contribute to PAH disease progression is unknown. Possible explanations could be worse RV function from chromium exposure or hypotension effects from chromium exacerbates RV ischemia and causes further deterioration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 In another human study of 62 patients, chromium levels were found significantly higher in patients with systolic ischemic heart disease. 33 The exact mechanisms of how chromium contribute to PAH disease progression is unknown. Possible explanations could be worse RV function from chromium exposure or hypotension effects from chromium exacerbates RV ischemia and causes further deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis of 11 eligible randomized controlled trials with 637 participants indicated that supplementation with chromium significantly decrease blood pressures 32 . In another human study of 62 patients, chromium levels were found significantly higher in patients with systolic ischemic heart disease 33 . The exact mechanisms of how chromium contribute to PAH disease progression is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported that the Chromium intakes at dose of 400 and 42 μg (in combination with 9 g brewer's yeast) during 12 and 4 weeks have been related to SBP reduction [ 35 , 36 ]. Moreover, in a study, individuals with systolic dysfunction have been shown with higher serum Chromium levels compared to those with normal systolic function [ 37 ]. A systematic reviews and meta-analyses also indicated that Chromium supplementation may have protective effects against myocardial infarction, reduce CVD-associated inflammatory biomarkers [ 13 ], and decrease DBP [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma chromium levels have also been reported to be negatively correlated with blood pressure and low-density lipoproteins [44]. However, another study reported that individuals with systolic dysfunction had increased serum chromium levels compared to those with normal systolic function [45]. A cross-sectional study reported that increasing circulating levels of chromium is associated with reduced lipid infiltration in the vascular wall (echogenicity of the intima-media complex) in the elderly [46].…”
Section: Introductionmentioning
confidence: 99%